Isolated pancreatic and peripancreatic nodal tuberculosis: A single-centre experience. (April 2021) - Ray, Sukanta; Das, Kshaunish; Ghosh, Ranajoy
Isolated pancreatic and peripancreatic nodal tuberculosis may mimic pancreatic malignancy and may result in unnecessary surgery. Being a treatable disease, it is desirable to diagnose this condition without a laparotomy. Pancreatic tuberculosis should be considered in the differential diagnosis of a peripancreatic mass if the patient is young, residing in endemic tuberculosis regions, or has had a history of tuberculosis. We report our experience with pancreatic tuberculosis. Over a period of 12 years, we have managed 16 such patients, of whom 10 were diagnosed preoperatively. In six, the diagnosis was only made after extensive surgery. All 16 patients received antitubercular drugs and were well at a median follow-up of 52 months. Although pancreatic tuberculosis can be diagnosed by modern image-guided biopsy in a fair number of patients, if a high index of suspicion is maintained, a laparotomy may still be unavoidable in a subset of patients.